Surface modification of pvdf membrane using formic acid to enhance the hydrophobicity for desalination - Sunarti, Abd Rahman; Agamparam, Hematharshini (2021)
Membrane distillation (MD) is a new membrane separation technology using the temperature gradient created on membrane surfaces as a driving force. A few problems for practical application of membrane distillation process for desalination have to be settled, such as progressive wettability of the membrane. In this study to enhance the hydrophobicity of PVDF some modification made by treating the membrane with formic acid which is a simple and sustainable method of surface modification to eliminate fluorine atom.